Using consumer search cost and loyalty to explain dispersion in banking fees - Lopes, Manuela Hungerbühler (2011)
Prices of a homogenous package of services present considerable dispersion across banks. A simple model that uses consumer search costs and loyalty is devolped in order to reproduce this empirical observation. Using data for the brazilian banking sector, empirical exercises are performed to allow for: (i) the estimation of consumer search costs by xing the values of other parameters; and (ii) the estimation of the corresponding deadweightlosses imposed by costly search. When only 80% of the population is free to engage in search activity, at a 0.5% monthly interest rate, the upper limit of the support of the search cost distribution is found to be 1805.80 BRL. In this case, the corresponding estimate of the deadweightloss imposed on an average searcher is 233.71 BRL.